Mengungkap Kebijakan Akuntansi Agrikultur Pada Tiga Kementerian Negara/Lembaga - Okky Dwi Berliantonnis; Puji Wibowo (Akuntansiku, 2022)
Indonesia is a country that has been blessed  with abundant natural resources, including plants and animals. In the context of accounting, natural resources in this form are classified as biological assets or agricultural assets. The growing development of biological asset transactions in both the private and government sectors has presented its own challenges for the development of accounting standards. Agricultural accounting practices in government agencies are increasingly attractive because until now there is no accounting standard that specifically regulates the accounting treatment of agricultural assets in government agencies. This study aims to review agricultural accounting policies and practices in central government entities. The object of research is the Ministry of Maritime Affairs and Fisheries, the Ministry of Environment and Forestry and the Ministry of Agriculture, during the 2018-2019 period. This research uses qualitative analysis with a case study approach. The results showed that in general, the application of agricultural accounting at the three State Ministries/Institutions was in accordance with the relevant government accounting standards, namely inventory accounting and fixed assets/other assets. However, when referring to the International Public Sector Accounting Standard, there are still some accounting practices that need to be improved, especially in the measurement aspect. This research contributes to empirical evidence of the non-uniformity of agricultural accounting practices as a result of the absence of accounting standards that specifically regulate these assets. Formulators of government accounting standards are expected to immediately establish accounting standards that specifically regulate agricultural assets in government agencies. Indonesia merupakan negara yang dianugerahi kekayaan alam yang berlimpah, diantaranya tanaman, tumbuhan dan binatang. Dalam konteks akuntansi, kekayaan alam dalam bentuk tersebut digolongkan sebagai aset biologi atau aset agrikultur. Perkembangan transaksi aset biologis yang semakin besar baik di sektor swasta dan pemerintah, telah menghadirkan tantangan tersendiri bagi pengembangan standar akuntansi. Praktik akuntansi agrikultur pada instansi pemerintah kian menarik karena hingga saat ini belum terdapat standar akuntansi yang secara khusus mengatur perlakuan akuntansi aset agrikultur pada instansi pemerintah. Penelitian ini bertujuan untuk meninjau kebijakan dan praktik akuntansi agrikultur pada entitas pemerintah pusat. Objek penelitian adalah Kementerian Kelautan dan Perikanan, Kementerian Lingkungan Hidup dan Kehutanan dan Kementerian Pertanian, selama periode 2018-2019. Riset ini menggunakan analisis kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan bahwa secara umum, penerapan akuntansi agrikultur pada tiga Kementerian Negara/Lembaga tersebut telah sesuai dengan standar akuntansi pemerintahan yang terkait yaitu akuntansi persediaan dan aset tetap/aset lainnya. Namun demikian, jika mengacu pada International Public Sector Accounting Standard, masih terdapat beberapa praktik akuntansi yang perlu diperbaiki, khususnya dalam aspek pengukuran. Riset ini memberikan kontribusi mengenai bukti empiris adanya ketidakseragaman praktik akuntansi agrikultur sebagai akibat ketiadaan standar akuntansi yang secara khusus mengatur aset tersebut. Perumus standar akuntansi pemerintahan diharapkan dapat segera menetapkan standar akuntansi yang mengatur secara khusus mengenai aset agrikultur pada instansi pemerintah.